Joulukellot kaikuu = Julklockorna ringa : op. 32, nr. 1 - Kotilainen, Otto, 1868-1936; Runeberg, Nino, 1874-1934; Kaukonen, Vilppu, 1868-1923; Kotilainen, Otto, 1868-1936.; Kotilainen, Otto, 1868-1936. (Helsinki = Helsingfors : A/B R. E. Westerlund O/Y, [1920], 1920)
1 kappale.
Joulukellot kaikuu = Julklockorna ringa.
Musiikin esityskokoonpano: lauluääni, piano.
Sävellysvuosi viimeistään 1920.
Sanat: suomi, ruotsi.
Keywords: joululaulut